Platelet count and platelet‐lymphocyte ratio as prognostic markers for head and neck squamous cell carcinoma: Meta‐analysis. Issue 12 (13th August 2018) - Takenaka, Yukinori; Oya, Ryohei; Kitamiura, Takahiro; Ashida, Naoki; Shimizu, Kotaro; Takemura, Kazuya; Yamamoto, Yoshifumi; Uno, Atsuhiko
Abstract: Background: Thrombocytosis is associated with the prognosis of various types of cancer. The purpose of this study was to quantify the prognostic impact of platelet count and platelet‐lymphocyte ratio (PLR) in head and neck squamous cell carcinoma (HNSCC). Methods: We systematically searched electronic databases and identified articles reporting an association between platelet count or PLR and HNSCC prognosis. Hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS) were extracted, and the pooled HRs were estimated using random effect models. Results: Eight studies that enrolled 4096 patients and 9 studies that enrolled 2327 patients were included in the platelet count and PLR analyses, respectively. A platelet count greater than the cutoff value was associated with poor OS (HR 1.81; 95% CI 1.16‐2.82) and any PLR greater than the cutoff value was associated with poor OS (HR 1.64; 95% CI 1.13‐2.37). Conclusion: Elevated platelet count and PLR are associated with poor prognosis in patients with HNSCC.